Recent Advancements of Nano-Biosensors in Nanotheranostics: An Update - Jyoshna Rani Dash; Gurudutta Pattnaik; Subhranshu Acharya; Sasmita Dash; Goutam Ghosh; Goutam Rath; Biswakanth Kar (Current Drug Therapy, 2026)
Abstract: Nanotechnology has brought transformative advancements across numerous sectors, particularly in medicine. One of its most impactful applications lies in biomedical diagnostics, where the development of nanosensors has significantly enhanced the detec-tion and identification of disease-related biomarkers. These nanoscale devices leverage molecular recognition techniques to detect a wide array of biological and chemical substances with high sensitivity and specificity. Their utility spans various in vitro diagnostic applications, including the rapid and accurate quantifica-tion of pathogens, detection of genetic disorders, identification of disease biomarkers, and drug screening. The versatility of nanomaterials, owing to their diverse shapes, sizes, and surface modifications, has further improved the speed, sensitivity, and reproducibility of these diagnostic tools. In oncology, early detection remains a critical determinant of treatment success. However, conventional cancer diagnostic approaches often fall short due to limitations in sensitivity, specificity, and accessibility. To address these challenges, recent innovations have intro-duced multifunctional nanoparticles and nano-biosensors that selectively target tumor-spe-cific biomarkers using biocompatible ligands. These targeted nanosystems enable site-spe-cific delivery and imaging, paving the way for more accurate and non-invasive cancer di-agnostics. Recent developments in biosensor design, signal amplification strategies, and material functionalization have led to next-generation nano-biosensors with improved di-agnostic accuracy and lower detection limits. These platforms hold immense promise for point-of-care cancer diagnosis due to their rapid performance, cost-effectiveness, and potential for clinical translation. This review provides a comprehensive overview of the latest advancements and current trends in nano-biosensor technology as a promising tool in cancer diagnostics.